(untitled) (Journal of the College of Basic Education, 2023)
This research is concerned with the study of (design systems for the decorations of the Holy Quran) studyanalytical); It falls into four chapters; The first chapter is devoted to (statement of the problem of broadcastingits importance and need for it; its purpose and limits; Define the terms mentioned in the titleand definition). The research problem has been summarized in answering the following question:- What are the abstract design systems for Islamic decoration in the Holy Quran? The importance of the research was evident in the fact that it benefits those interested in decoration and Arabic calligraphy in one wayIn particular, by looking at the results and conclusions of the research. The researcher found that there is an essential need for this study. It consists of a universeThe subject has not been studied in such detail; And the lack of Mknbtna boredom of these studiesAcademic, which is concerned with the interior decorations in the Holy Quran The research has a comprehensive goal: to identify abstraction in the design systems of Islamic decorationsfor the Holy Quran; With regard to the limits of the research, it was determined by studying b (models from the Holy Qur’anIt was implemented in the Arab and Islamic regions and included publishing houses according to the following:(Iraq, Egypt, Saudi Arabia, Iran, Turkey). From the year (0721 H - to H) 1398The second chapter included the theoretical framework; And on previous studies 0 and eat